The administration of juvenile justice system in Malaysia: moving towards restorative justice process? - Ahmad, Nadzriah (Universiti Teknologi MARA, Perlis, 2011)
This article analyzes pertinent issues surrounding administration of juvenile justice system in Malaysia and examine whether restorative justice process should be incorporated into the system to make it in line with the Convention on the Rights of the Child 1989 and other international instruments.